Cross-country estimates of the degree of fiscal dominance and central bank independence - Carlos De Resende (Bank of Canada, 2007)
This paper studies the interdependence between fiscal and monetary policies, and their joint role in the determination of the price level. The government is characterized by a long-run fiscal policy rule whereby a given fraction of the outstanding debt, say , is backed by the present discounted value of current and future primary surpluses. The remaining debt is backed by seigniorage revenue. The parameter characterizes the interdependence between fiscal and monetary authorities. It is shown that in a standard monetary economy, this policy rule implies that the price level depends not only on the money stock, but also on the proportion of debt that is backed with money. Empirical estimates of are obtained for OECD and developing countries using data on nominal consumption, monetary base, and debt. Results indicate differences in the degree of fiscal dominance between developed and developing economies. Estimates of correlate positively with some institutional measures of de facto central bank independence.
Keywords: E31; E42; E50; E63; 330; Central bank research; Fiscal policy; Inflation: costs and benefits; Geldpolitik; Finanzpolitik; Geldbasis; Zentralbankautonomie; Preisniveaustabilität; Welt